Pembangunan Sistem Informasi Pelayanan Administrasi Rumah Sakit Bakti Timah Karimun Menggunakan Metode Prototyping - Jeni Aprilia; Muhammad Ihsan Zul (ABEC Indonesia, 2021)
Abstract Service is the provision of service either by the government, private parties on behalf of the government or private parties to the community with or without payment to meet the needs and interests of the community. Bakti Timah Karimun hospital is one of the private hospitals engaged in health services to the community. Currently, Bakti Timah Karimun Hospital has not implemented and utilized the existence of integrated information technology to support daily work activities so that most of the operational activities of health services are still carried out manually. Along with hospital operational activities, there are many obstacles that cause problems that interfere with daily activities. Because some activities are still done manually, it automatically makes it difficult and slows down hospital staff to serve patients. From these problems we need a system that can assist officers in providing services to patients. This study presents a Website-Based Service Information System that was built using PHP (Pearl Hypertext Processor) as the programming language and MySQL as the database. The system was built using the prototyping method and the CI framework. The system development was carried out for 5 months with 3 iterations. With this system, it is hoped that it can help overcome problems in providing service information to patients at the Bakti Timah Karimun Hospital. Keywords: Service Information System, Prototyping Method, Web, PHP, MySQL